Workshop on Natural Medicine Ingredients for Digestive System Disorders - Wibowo, Teguh Setiawan; Arif, Fahrudin; Pramono, Joko; Firdiansyah, Moh. Rofiqi; Ardiansyah, M. Yusuf; Purwantoro, Guntur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Traditional medicine is an ingredient or a combination of ingredients in the form of plant materials, animal materials, mineral materials, preparation of sarian (galenik) or a mixture of these materials that have been used for generations for treatment and can be applied in accordance with the norms prevailing in the community. One of the basic needs of living things is food and health. Food is needed by living things as a source of energy, therefore the food consumed must contain substances needed by the body, such as carbohydrates, proteins, fats, vitamins, minerals, and water. The digestive system in humans is a series of processes to convert food by breaking down complex food molecules into simple ones with the help of enzymes and absorbing the food essence needed by the human body. So that digestive system disorders greatly affect the human health system. The method used is presentation, question, answer, discussion and assistance (in the form of practice and evaluation) with preparation carried out for 2 weeks.